KIZOMBA - festa da consciência negra: um projeto escolar influenciado pelo Movimento Negro (Montenegro/RS de 1988 a 2002) - Conceição, Alexandre Ferraz da (Universidade do Vale do Rio dos Sinos, 2022)
The study deals with the perceptions of a school project called Kizomba – Festa da Consciência Negra. This took place between 1988 and 2002 at Escola Estadual de Ensino Fundamental Manoel de Souza Moraes, in Montenegro, Rio Grande do Sul. It aims to analyze the memories of teachers andformer students who participated in the project, seeking to understand, from their narratives, motivations, achievements, scope, and limitations of this school project. The methodology of oral history was used, and the produced narratives were analyzed under the foundations of Augustín Escolano Benito, Antonio Vinao Frago, Dominique Julia, Nilma Lino Gomes, Stuart Hall, Tomaz Tadeu da Silva, and Kathryn Woodward. The Kizomba project emerged in the context of the country's political redemocratization and the intense debates mobilized by the Black Movement. It can contribute to the institution's school culture. Within the empirical perspective, it is clear that this action dialogued with the struggles of the Black Movement, collaborating for the pedagogical formation on the ethnic-racial theme, still incipient in the period of execution of the project. The teacher awareness, revealed and assumed by the interviewed teachers, indicates the efforts undertaken by them to make the school a plural space in which ethnic differences should be respected. The dissertation presented, included in the History of Education, points out the approximations between the Black Movement and school institutions, especially the one that made the existence of Kizomba possible, as well as revealing the educational practices used in the project. It is emphasized that the execution of this project, which precedes the enactment of Law 10.639/2003, could be one of the tests that legitimized education for ethnic-racial relations, currently provided for in legal guidelines.
Keywords: Movimento negro; Cultura escolar; Projeto Kizomba; Black movement; School culture; Kizomba project; ACCNPQ::Ciências Humanas::Educação